Depolymerized carrageenan expresses elicitor-like activity on Mentha arvensis L. under arsenic stress Insights into arsenic resilience and monoterpene synthesis - Nabi, Aarifa (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.